Imaging gait analysis: An fMRI dual task study. Issue 8 (21st July 2017) - Bürki, Céline N.; Bridenbaugh, Stephanie A.; Reinhardt, Julia; Stippich, Christoph; Kressig, Reto W.; Blatow, Maria
Abstract: Introduction: In geriatric clinical diagnostics, gait analysis with cognitive‐motor dual tasking is used to predict fall risk and cognitive decline. To date, the neural correlates of cognitive‐motor dual tasking processes are not fully understood. To investigate these underlying neural mechanisms, we designed an fMRI paradigm to reproduce the gait analysis. Methods: We tested the fMRI paradigm's feasibility in a substudy with fifteen young adults and assessed 31 healthy older adults in the main study. First, gait speed and variability were quantified using the GAITRite © electronic walkway. Then, participants lying in the MRI‐scanner were stepping on pedals of an MRI‐compatible stepping device used to imitate gait during functional imaging. In each session, participants performed cognitive and motor single tasks as well as cognitive‐motor dual tasks. Results: Behavioral results showed that the parameters of both gait analyses, GAITRite © and fMRI, were significantly positively correlated. FMRI results revealed significantly reduced brain activation during dual task compared to single task conditions. Functional ROI analysis showed that activation in the superior parietal lobe (SPL) decreased less from single to dual task condition than activation in primary motor cortex and in supplementary motor areas. Moreover, SPL activation was increased during dual tasks in subjects exhibiting lower stepping speed and lower executive control. Conclusion: We were able to simulate walking during functional imaging with valid results that reproduce those from the GAITRite © gait analysis. On the neural level, SPL seems to play a crucial role in cognitive‐motor dual tasking and to be linked to divided attention processes, particularly when motor activity is involved. Abstract : Gait alterations under a dual task condition, that is, walking while simultaneously performing a cognitive task, provide an indicator for changes in attentional processes, which is used in geriatric clinical diagnostics to predict fall risk and cognitive decline. This study investigates the neural correlates of cognitive‐motor dual tasking processes during gait analysis by means of fMRI with an MR‐compatible stepping device in young and old adults. Results suggest that an area in the superior parietal lobe plays a crucial role in cognitive‐motor dual tasking and therefore is linked to divided attention processes particularly when motor activity is involved.